2022
DOI: 10.3390/universe8090472
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Large-Scale Solar-Wind Streams Obtained by the Double Superposed Epoch Analysis: 5. Influence of the Solar Activity Decrease

Abstract: In solar cycles 23–24, solar activity noticeably decreased and, as a result, solar wind parameters decreased. Based on the measurements of the OMNI base for the period 1976–2019, the time profiles of the main solar wind parameters and magnetospheric indices for the main interplanetary drivers of magnetospheric disturbances (solar wind types CIR. Sheath, ejecta and MC) are studied using the double superposed epoch method. The main task of the research is to compare time profiles for the epoch of high solar acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 29 publications
5
11
0
1
Order By: Relevance
“…Region r 5 contains a local peak in P t , a decreasing N p , gradually increasing V sw and T p , and local peak at B. This satisfies the SIR identification criteria suggested by Jian et al (2006), Lepping et al (1997), andYermolaev et al (2022). Yermolaev et al (2022) performed a superposed epoch analysis of solar wind parameters for corotating interaction regions (CIRs) with and without a preceding interplanetary shock wave during high and low solar activity periods and observed a decrease in n p and enhancement in T p , B, V sw , and thermal pressure.…”
Section: In Situ Analysissupporting
confidence: 53%
See 1 more Smart Citation
“…Region r 5 contains a local peak in P t , a decreasing N p , gradually increasing V sw and T p , and local peak at B. This satisfies the SIR identification criteria suggested by Jian et al (2006), Lepping et al (1997), andYermolaev et al (2022). Yermolaev et al (2022) performed a superposed epoch analysis of solar wind parameters for corotating interaction regions (CIRs) with and without a preceding interplanetary shock wave during high and low solar activity periods and observed a decrease in n p and enhancement in T p , B, V sw , and thermal pressure.…”
Section: In Situ Analysissupporting
confidence: 53%
“…This satisfies the SIR identification criteria suggested by Jian et al (2006), Lepping et al (1997), andYermolaev et al (2022). Yermolaev et al (2022) performed a superposed epoch analysis of solar wind parameters for corotating interaction regions (CIRs) with and without a preceding interplanetary shock wave during high and low solar activity periods and observed a decrease in n p and enhancement in T p , B, V sw , and thermal pressure. However, they found that the temporal profile of β remains at nearly 1 during the CIR crossings.…”
Section: In Situ Analysismentioning
confidence: 76%
“…It can be noted that the tendency for T to increase during the rising phase of SC 25 is observed only for quasistationary SW types (HCS, Slow, and Fast) and is not observed for disturbed SW types (CIR, Sheath, Ejecta, and MC). Since the number of disturbed SW types is small during this period (see, e.g., [Yermolaev et al, 2023]), the T behavior for the sum of all types (All) is similar to the behavior for quasi-stationary SW types.…”
Section: Resultsmentioning
confidence: 75%
“…The prediction of the development of solar activity in the coming years and, in particular, in SC 25 remains debatable and is widely discussed in the literature [Du, 2023;Peguero, Carrasco, 2023;Coban et al, 2021;Nagovitsyn, Ivanov, 2023;Prasad et al, 2023;Zharkova et al, 2023;Javaraiah, 2023]. We hope that the results reported in this paper will provide a deeper insight into the development of solar activity in the current solar cycle and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand how the decrease in solar activity in solar cycles 23-24 affected the main drivers of magnetospheric disturbance, Yermolaev et al [8] studied the average temporal profiles of the solar wind parameters and magnetospheric indices of the disturbed solar wind types CIR, Sheath, ejecta, and MC and found that the profiles remained similar in shape but noticeably decreased in magnitude. In another work, Yermolaev et al [9] discussed the general effects of changes in the structure of the heliosphere and the decrease in the solar wind parameters on the solar wind/magnetosphere interaction.…”
mentioning
confidence: 99%